The Media, European Integration and the Rise of Euro-journalism, 1950s–1970s - Herzer, Martin. author. aut Link
XIV, 357 p. 1 illus.
Keywords: This book explains how the media helped to invent the European Union as the supranational polity that we know today. Against conventional EU scholarship, it tells the story of the rise of the Euro-journalists – pro-European advocacy journalists – within the post-war Western European media, and argues that the Euro-journalists pioneered a shift in the media representation of European integration. During the 1950s, multiple visions of Western European cooperation competed in the media, which initially considered the European Community to be a merely technocratic international organization. By the late 1970s, however, the media were symbolically magnifying the Community as a sui generis European polity and the sole embodiment of Europe. Normative research on the media and European integration has focused on how the media might help to construct a democratic and legitimate European Union. In contrast, this book aims to deconstruct a pro-European advocacy journalism, which became dominant within the Western European media between the 1950s and the 1970s. Moreover, the book shows how journalists – as part of Western European elites – played a key role in elite European identity building campaigns.